Investigation of inter-annual variation in the feeding habits of Japanese sardine (Sardinops melanostictus) and mackerels (Scomber spp.) in the Western North Pacific based on bulk and amino acid stable isotopes - Ohno, Yosuke; Umezawa, Yu; Okunishi, Takeshi; Yukami, Ryuji; Kamimura, Yasuhiro; Yoshimizu, Chikage; Tayasu, Ichiro (Frontiers in Marine Science, 2023)
Inter-annual variation in the feeding habits and food sources of Japanese sardine and mackerel at age-0 and age-1+ caught in the Kuroshio-Oyashio transition zone of the Western North Pacific were investigated based on analyses of bulk stable isotopes (δ13C, δ15N) and amino acid nitrogen isotopes (δ15NAA). Differences in δ13C and δ15N between Japanese sardine and mackerel were small for age-0, and inter-annual variation trends were similar, suggesting they depend on similar food sources in the same food web at this age. In contrast, inter-annual variation in δ13C and δ15N were significantly different between both species at age-1+, and both δ15N of phenylalanine (δ15NPhe: an indicator of nitrogen source) and trophic position estimated from δ15NAA (TPAA) were higher in mackerel, suggesting that the two species depend on distinct food webs as they age. Inter-annual variations in δ15NPhe were considered to have different causes for the two species; differences in food web structure due to the degree of southward intrusion of the Oyashio Current for Japanese sardine, compared to a shift in migration area and depth for mackerel. Furthermore, competition for food due to the recent increases in the population densities of both fishes appeared to be reflected in increased TPAA of mackerel. Although they are caught in the same region, the mechanism of variation in food sources differs because of differences in migration area, depth, and feeding habits. Differences in the feeding habits of Japanese sardine and mackerel may affect trophic status and spawning characteristics, potentially leading to different shifts in stock abundances.